Effect of Spacing on Sleeper Lateral Resistance Supplementary Data - Jacob Whittle (11486803) (2025)
Data supporting the publication titled "Evaluating the effect of spacing on the lateral resistance of steel and concrete sleepers using a novel methodology". Data comprising multi-sleeper lateral resistance and lateral displacement acquired in a laboratory based ballast box and processed to remove the contribution of uplift forces as described with the accompanying publication. Data is stored as a combined CSV file for tests 1 - 42 (1-21 Concrete G44, 22-42 Steel W560H) .